HUBUNGAN LETAK LESI STROKE TERHADAP SIMTOM DEPRESI PADA PASIEN PASCA STROKE DI RSUD DELI SERDANG - NAUFAL MUHAMMAD ZAHRAN; ANITA SURYA (JURNAL ILMIAH SIMANTEK, 2021)
Stroke is a sudden functional focal and global brain disorder and can cause sudden death caused by impaired cerebralblood flow due to reduced blood supply (ischemic stroke) or spontaneous rupture of blood vessels (bleeding strokes).Depression is a neuropsychiatric syndrome that is most often associated with stroke. To determine the relationship ofthe location of the stroke lesion on depressive symptoms in post-stroke patients at Deli Serdang Regional Hospitalwhich was conducted from August to December 2019. Categorical analytic using cross sectional design.Outpatient stroke patients are classified as patients with left or right hemisphere lesions. The research data wereobtained from primary data in the form of direct interviews with patients using the Beck Depression Inventory-II (BDI-II)questionnaire and also from secondary data in the form of patient medical records at the Hospital which included 64patients and then analyzed using the Chi Square test. Chi Square test results showed that there was a significantrelationship between the location of the stroke lesion on the incidence of depression with a value of P = 0.006 (p<0.05).